High-uv-resistant two-component polyurethane sealant, preparation method and application thereof

CN122542191BActive Publication Date: 2026-10-13中国铁建投资集团有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611039731.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-10-13
Estimated Expiration
2046-07-14

AI Technical Summary

Technical Problem

[0005]本发明的第一目的是提供一种高耐紫外双组份聚氨酯密封胶,用于解决现有密封胶粘结强度不够、弹性不好、在耐紫外辐照性能不佳、性能不稳定的问题

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_13
    Figure SMS_13
Patent Text Reader

Abstract

The application provides a high-UV-resistant two-component polyurethane sealant and a preparation method and application thereof. The high-UV-resistant two-component polyurethane sealant comprises component A and component B. The component A comprises a prepolymer first polyether polyol, a first filler and a first additive. The prepolymer comprises a first isocyanate, a second polyether polyol, a polyester polyol and a first catalyst. The first filler comprises a UV-resistant filler accounting for 10-30% of the mass of the component A. The first additive comprises a UV-resistant additive accounting for 0.1-1% of the mass of the component A. The component B comprises a second isocyanate, a second filler and a second additive. The mass ratio of the component A to the component B is (8-16):1. In the application, the sealant with a cross-linking structure is prepared by using polyols, and the UV-resistant filler and the UV-resistant additive are used to effectively improve the UV resistance of the sealant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of adhesive technology, specifically to a high UV-resistant two-component polyurethane sealant, its preparation method, and its application. Background Technology

[0002] Sealant is a material used to fill gaps (holes, seams, etc.). Elastic sealant combines both bonding and sealing functions. The sealant for double-glazed insulated glass is a special product used in the construction industry. Double-glazed insulated glass is a window glass product consisting of two panes of glass sealed around the edges, with dry air or a vacuum filling the space between them. It has excellent thermal insulation properties and is mainly used for doors and windows. In the mainstream double-seal manufacturing process for insulated glass, the first seal uses butyl rubber, and the second seal uses polysulfide (PS), silicone (SR), or polyurethane (PU) elastic sealant.

[0003] Currently, the mainstream elastic sealant used in insulated glass is silicone sealant, which has good weather resistance and is easy to apply. However, its long-term airtightness is generally poor, and it is prone to problems such as small-molecule oil seepage, large price fluctuations, and market instability. Polysulfide sealant has good long-term airtightness and excellent performance, but it has a strong odor during construction, which can affect the health of construction workers.

[0004] Polyurethane sealant is an environmentally friendly material with stable raw material prices, low water vapor permeability and water absorption, and good airtightness. However, most polyurethane sealants currently on the market require a primer to ensure good adhesion to glass, have low strength, and also suffer from poor resistance to ultraviolet radiation. Summary of the Invention

[0005] The primary objective of this invention is to provide a high UV-resistant two-component polyurethane sealant to address the problems of insufficient bonding strength, poor elasticity, inadequate UV radiation resistance, and unstable performance of existing sealants.

[0006] The second objective of this invention is to provide a method for preparing a high UV-resistant two-component polyurethane sealant, for use in preparing the aforementioned high UV-resistant two-component polyurethane sealant.

[0007] A third objective of this invention is to provide the application of the aforementioned high UV-resistant two-component polyurethane sealant in insulated glass.

[0008] To achieve the aforementioned first objective, the present invention provides a high UV-resistant two-component polyurethane sealant, comprising component A and component B. By weight percentage, component A comprises 40%–60% prepolymer, 5%–10% first polyether polyol, 30%–50% first filler, and 0.1%–5% first additive; wherein, by weight percentage, the prepolymer comprises 10%–20% first isocyanate, 8%–15% second polyether polyol, and 65%–75% polyester polyol. The first catalyst comprises 0.1% to 0.5% of component A; the first filler comprises 10% to 50% of UV-resistant filler by mass of component A; the first auxiliary agent comprises 0.1% to 3% of UV-resistant auxiliary agent by mass of component A; component B comprises 85% to 95% of second isocyanate, 1% to 5% of second filler and 1.1% to 10.5% of second auxiliary agent by mass percentage; wherein the mass ratio of component A to component B is (8 to 16):1; the UV-resistant filler comprises titanium dioxide and / or nano zinc oxide.

[0009] As can be seen from the above scheme, the high UV-resistant two-component polyurethane sealant provided by the present invention, through the independent synthesis of hydroxyl-terminated prepolymer, is mixed with polypropylene triol and then reacted with the corresponding isocyanate component. The molecular weight and crosslinking density of the final reaction product are adjusted, which firstly achieves that the interfacial adhesion between the sealant and glass is greater than the cohesive force of the sealant. Furthermore, by using UV-resistant fillers and UV-resistant additives, UV irradiation can effectively prevent damage to the molecular structure of the material, maintain its original tensile strength, elasticity, adhesion, and sealing properties, ensure the safety and reliability of the sealant, and extend the service life of the sealant. Among them, the UV-resistant filler can form a physical barrier by reflecting and scattering UV light.

[0010] A further approach is to include UV-resistant additives such as UV absorbers and / or hindered amine light stabilizers.

[0011] A further option is to select one or more of the following: benzotriazoles, triazines, benzophenones, and benzylmalonates.

[0012] As can be seen from the above scheme, the UV absorber in the UV-resistant additive can efficiently absorb UV light and convert high energy into harmless heat energy through intramolecular hydrogen bond tautomerism; the hindered amine light stabilizer scavenges free radicals and does not absorb UV light. Thus, it can effectively prevent UV irradiation from damaging the molecular structure of the material, maintain its original tensile strength, elasticity, adhesion and sealing properties, ensure the safety and reliability of the sealant, and extend the service life of the sealant.

[0013] A further embodiment is that the high UV-resistant two-component polyurethane sealant meets at least one of the following conditions: 1) the first polyether polyol in component A includes polyoxypropylene triol; 2) the first filler in component A further includes one or more of nano-calcium carbonate, heavy calcium carbonate, and talc; 3) the first additive in component A further includes 0% to 2% by mass of a first coupling agent; 4) the first isocyanate in the prepolymer includes one or more of toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate; 5) the second polyether polyol in the prepolymer includes poly... 6) The polyester polyol in the prepolymer includes polycarbonate diol; 7) The first catalyst in the prepolymer includes an organometallic catalyst; 8) The second isocyanate in component B includes one or more of diphenylmethane diisocyanate, isophorone diisocyanate and hexamethylene diisocyanate trimer; 9) The second filler in component B includes carbon black; 10) The second auxiliary agent in component B includes a second coupling agent accounting for 1% to 10% of the mass of component B and a second catalyst accounting for 0.1% to 0.5% of the mass of component B, wherein the second catalyst includes an organometallic catalyst.

[0014] A further option is that the high UV-resistant two-component polyurethane sealant meets at least one of the following conditions: 1) the molecular weight of polypropylene triol in component A is one or more of 300, 400, 500, 700 and 1000; 2) the molecular weight of polypropylene glycol in the prepolymer is one or more of 200, 400, 600, 1000, 1500 and 2000; 3) the molecular weight of ethylene glycol in the prepolymer is one or more of 200, 400 and 600; 4) the molecular weight of polycarbonate glycol in the prepolymer is 1000 and / or 2000.

[0015] A further option is that the high UV-resistant two-component polyurethane sealant meets at least one of the following conditions: 1) the organometallic catalyst includes one or more of dibutyltin dilaurate, stannous octoate, lead isooctanoate, zinc bismuth composite catalyst, bismuth isooctanoate, and zinc neodecanoate; 2) the first coupling agent in component A includes one or more of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-aminopropyltriethoxysilane, bis-(γ-trimethoxysilylpropyl)amine, and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane; 3) the second coupling agent in component B includes one or more of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 3-isocyanate-propyltrimethoxysilane, and 3-isocyanate-propyltriethoxysilane.

[0016] As can be seen from the above scheme, after adding appropriate coupling agents to components A and B, the coupling agents can interact with both the hydroxyl groups in inorganic materials and the long molecular chains in organic polymers, thus coupling the two materials with different properties together. This enhances the interfacial interaction between the two-component polyurethane sealant and the glass, further increases the adhesion between the two-component polyurethane sealant and the glass interface, and can thus achieve cohesive failure.

[0017] Furthermore, by adding trifunctional polyoxypropylene alcohol, the crosslinking density of polyurethane sealant can be increased, thereby enhancing its strength, rigidity, and UV resistance.

[0018] The second isocyanate uses hexamethylene diisocyanate trimer, which can further increase the crosslinking density of polyurethane sealant, thereby increasing the strength, rigidity and UV resistance of polyurethane sealant.

[0019] The second filler is carbon black, which can both color the material and increase the viscosity of component B.

[0020] To achieve the second objective mentioned above, the present invention provides a method for preparing a high UV-resistant two-component polyurethane sealant. The method comprises the following steps: S1: Preparation of the prepolymer: reacting a first isocyanate with a second polyether polyol and a polyester polyol to obtain a prepolymer; S2: Preparation of component A: mixing the prepolymer, the first polyether polyol, the first filler, and the first additive, followed by heat treatment and dehydration, to obtain component A; S3: Preparation of component B: dehydrating the second filler, then adding the second isocyanate and the second additive and mixing evenly to obtain component B; S4: Preparation of the sealant: mixing component A and component B at a mass ratio of (8~16):1 and then curing to obtain the high UV-resistant two-component polyurethane sealant.

[0021] A further approach is that the preparation method satisfies at least one of the following conditions: 1) The preparation of the prepolymer in step S1 specifically includes: mixing the second polyether polyol and the polyester polyol and heating to 100℃~120℃, dehydrating under vacuum for 0.5h~2h, cooling down, adding the second catalyst, adding the first isocyanate and stirring to react, thereby obtaining the prepolymer; 2) The preparation of component A in step S2 specifically includes: mixing the prepolymer, the first polyether polyol and the first filler and heating to 100℃~130℃, dehydrating under vacuum for 1h~4h, until... The water content is reduced to below 500 ppm to obtain a premix; the premix is ​​cooled to below 60°C, the first additive is added, and the mixture is stirred evenly under vacuum to obtain component A; 3) The preparation of component B in step S3 specifically includes: placing the second filler in a high-speed planetary dispersion mixer, heating it to 80°C~100°C, dehydrating it under vacuum for 2h~4h until the water content of the second filler is reduced to below 1000 ppm, cooling the temperature of the second filler to room temperature, adding the second isocyanate and the second additive, and mixing evenly under vacuum until the viscosity is (5×10) 4 )mPa s~(8×10 4 )mPa s, to obtain component B.

[0022] A further embodiment is that the preparation method satisfies at least one of the following conditions: 1) The temperature at which the second catalyst is added in step S1 is 50℃~60℃; 2) The first isocyanate is added dropwise in step S1 for 30min~60min; 3) The reaction temperature at which the first isocyanate is added in step S1 is 70℃~80℃, the reaction time is 2h~4h, and the reaction atmosphere is nitrogen; 4) The stirring rate at which the first isocyanate is added in step S1 is 300r / min~500r / min; 5) The vacuum degree in step S2 is ≥0.09MPa; 6) The stirring rate at which mixing and stirring are performed in step S2 is 50r / min~400r / min; 7) The vacuum degree in step S3 is ≥0.09MPa; 8) The stirring rate at which uniform mixing is achieved in step S3 is 50r / min~400r / min.

[0023] As can be seen from the above scheme, the two-component polyurethane sealant prepared by the above preparation method has the characteristics of high bonding strength, good elasticity, stable performance and high UV resistance.

[0024] To achieve the third objective mentioned above, the present invention provides an application of a high UV-resistant two-component polyurethane sealant in insulated glass as described in any of the above embodiments.

[0025] As can be seen from the above scheme, the application of the above-mentioned high UV-resistant two-component polyurethane sealant to insulating glass has the characteristics of high bonding strength, good elasticity, stable performance and high UV resistance. Detailed Implementation

[0026] To facilitate understanding of this application, a more complete description will be provided below. However, this application can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of this application.

[0027] For simplicity, this application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form a range not explicitly stated; and any lower limit can be combined with other lower limits to form a range not explicitly stated, just as any upper limit can be combined with any other upper limit to form a range not explicitly stated. Furthermore, although not explicitly stated, every point or individual value between the endpoints of the range is included within that range. Therefore, each point or individual value can be used as its own lower or upper limit and combined with any other point or individual value or with other lower or upper limits to form a range not explicitly stated.

[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein in the specification of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. It should be noted that, unless otherwise stated, the term "and / or" as used herein includes any and all combinations of one or more of the associated listed items, "above," "below," includes the stated number, and "one or more" with "multiple" means two or more.

[0029] The foregoing description of this application is not intended to describe every disclosed implementation or method. Instead, the following description provides more specific examples of exemplary embodiments. Throughout the application, guidance is provided through a series of embodiments that can be used in various combinations. The examples listed are representative only and should not be construed as exhaustive.

[0030] This invention provides a high UV-resistant two-component polyurethane sealant, comprising component A and component B.

[0031] By weight percentage, component A comprises 40% to 60% prepolymer, 5% to 10% first polyether polyol, 30% to 50% first filler, and 0.1% to 5% first additive; The prepolymer comprises, by mass percentage, 10% to 20% of a first isocyanate, 8% to 15% of a second polyether polyol, 65% to 75% of a polyester polyol, and 0.1% to 0.5% of a first catalyst; The first filler includes UV-resistant filler accounting for 10% to 50% of the mass of component A; The first auxiliary agent includes a UV-resistant auxiliary agent accounting for 0.1% to 3% of the mass of component A; By mass percentage, component B comprises 85%–95% of the second isocyanate, 1%–5% of the second filler, and 1.1%–10.5% of the second auxiliary agent; The mass ratio of component A to component B is (8~16):1.

[0032] In some embodiments, the UV-resistant filler includes titanium dioxide and / or nano zinc oxide.

[0033] In some embodiments, the UV-resistant additives include UV absorbers and / or hindered amine light stabilizers. The UV absorbers are selected from one or more of benzotriazoles, triazines, benzophenones, and benzylmalonates. Preferably, the UV absorbers include one or more of UV234, UV326, UV328, UV329, UV1164, UV1577, UV630, UV531, and UV1988; the hindered amine light stabilizers include one or more of Tinuvin 770, Tinuvin 292, and Hostavin N30P.

[0034] In some embodiments, the first polyether polyol in component A includes polyoxypropylene triol, which has a molecular weight of one or more of 300, 400, 500, 700 and 1000.

[0035] In some embodiments, the first filler in component A may include other conventional fillers in addition to UV-resistant fillers. The types of other conventional fillers are not particularly limited and can be selected according to actual needs. Preferably, they may be one or more of nano-calcium carbonate, heavy calcium carbonate, and talc.

[0036] In some embodiments, the first adjuvant in component A further includes 0% to 2% by mass of a first coupling agent. The first coupling agent includes one or more of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-aminopropyltriethoxysilane, bis-(γ-trimethoxysilylpropyl)amine, and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane. Preferably, the first coupling agent includes one or more of KH-560, KH-550, Momentive A-1170, and KH-792.

[0037] In some embodiments, the first isocyanate in the prepolymer includes one or more of toluene diisocyanate (TDI-80), diphenylmethane diisocyanate (MDI-50, MDI-100), isophorone diisocyanate (IPDI), and hexamethylene diisocyanate (HDI).

[0038] In some embodiments, the second polyether polyol in the prepolymer includes polypropylene glycol and / or polyethylene glycol, wherein the polypropylene glycol has a molecular weight of one or more of 200, 400, 600, 1000, 1500 and 2000, and the polyethylene glycol has a molecular weight of one or more of 200, 400 and 600.

[0039] In some embodiments, the polyester polyol in the prepolymer includes polycarbonate diol with a molecular weight of 1000 and / or 2000.

[0040] In some embodiments, the first catalyst in the prepolymer comprises an organometallic catalyst, preferably one or more of dibutyltin dilaurate, stannous octoate, lead isooctanoate, zinc bismuth composite catalyst, bismuth isooctanoate, and zinc neodecanoate.

[0041] In some embodiments, the second isocyanate in component B includes one or more of diphenylmethane diisocyanate (MDI-50, MDI-100), isophorone diisocyanate (IPD), and hexamethylene diisocyanate trimer (HDI trimer). Preferably, the use of HDI trimer can further increase the crosslinking density of the polyurethane sealant, thereby increasing the strength, rigidity, and UV resistance of the polyurethane sealant.

[0042] In some embodiments, the second filler in component B includes carbon black. The type of carbon black is not particularly limited and can be selected according to actual needs. Preferably, it may include one or more of Cabot N220, Cabot N330, and Cabot N550.

[0043] In some embodiments, the second auxiliary agent in component B includes a second coupling agent comprising 1% to 10% of the mass of component B and a second catalyst comprising 0.1% to 0.5% of the mass of component B. The second catalyst includes an organometallic catalyst. The second coupling agent includes one or more of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 3-isocyanopropyltrimethoxysilane, and 3-isocyanopropyltriethoxysilane. Preferably, the second coupling agent includes one or more of KH-560, A-LINK35, and A-LINK25. The second catalyst can be the same as or different from the first catalyst, and can be selected according to actual needs. Preferably, it can include one or more of dibutyltin dilaurate, stannous octoate, lead isooctanoate, zinc bismuth composite catalyst, bismuth isooctanoate, and zinc neodecanoate.

[0044] This invention provides a method for preparing the above-mentioned high UV-resistant two-component polyurethane sealant, the method comprising the following steps: S1: Preparation of prepolymer: The first isocyanate is reacted with the second polyether polyol and the polyester polyol to obtain the prepolymer; S2: Preparation of component A: The prepolymer, the first polyether polyol, the first filler and the first auxiliary agent are mixed and then subjected to heat treatment and dehydration treatment to obtain component A; S3: Preparation of component B: After dehydrating the second filler, add the second isocyanate and the second auxiliary agent and mix evenly to obtain component B; S4: Preparation of sealant: Mix component A and component B at a mass ratio of (8~16):1 and then cure to obtain a high UV resistant two-component polyurethane sealant.

[0045] In some embodiments, the preparation of the prepolymer in step S1 specifically includes: mixing the second polyether polyol and the polyester polyol and heating to 100°C~120°C, dehydrating under vacuum for 0.5h~2h, cooling down and adding the second catalyst, adding the first isocyanate and stirring to react, thereby obtaining the prepolymer.

[0046] Preferably, in step S1, the second polyether polyol and the polyester polyol are second polyether polyol and polyester polyol that have undergone dehydration treatment.

[0047] Preferably, in step S1, the temperature at which the second catalyst is added is 50°C to 60°C, the stirring speed is 50 r / min to 400 r / min, and the mixing time is 5 min to 10 min.

[0048] Preferably, the first isocyanate is added in step S1 by slow dripping over a period of 30 to 60 minutes.

[0049] Preferably, the reaction temperature for adding the first isocyanate in step S1 is 70℃~80℃, the reaction time is 2h~4h, and the reaction atmosphere is a nitrogen atmosphere.

[0050] Preferably, the stirring rate for adding the first isocyanate in step S1 is 300 r / min to 500 r / min.

[0051] As a non-limiting example of preparing component A prepolymer, a second polyether polyol and a polyester polyol were added to a reactor according to the specified ratio. The reactor was heated to 100℃~120℃ at a rotation speed of 50 rpm~400 rpm and dehydrated under vacuum for 0.5 h~2 h until the water content was reduced to below 100 ppm. The temperature was then lowered to 50℃-60℃, and the catalyst was added and mixed thoroughly at a rotation speed of 50 rpm~400 rpm. Then, the first isocyanate was added dropwise at a rotation speed of 300 rpm~500 rpm and reacted at 70℃~80℃ for 2 h~4 h under nitrogen protection to obtain the prepolymer, which was then sealed and stored for later use.

[0052] In some embodiments, the preparation of component A in step S2 specifically includes: mixing the prepolymer, the first polyether polyol and the first filler and heating to 100°C~130°C, dehydrating under vacuum for 1h~4h until the water content drops below 500ppm to obtain a premix; cooling the premix to below 60°C, adding the first additive, and mixing and stirring evenly under vacuum to obtain component A.

[0053] Preferably, the vacuum level in step S2 is 0.09 MPa or higher.

[0054] Preferably, the mixing speed in step S2 is 50 r / min to 400 r / min.

[0055] As a non-limiting example of preparing component A, the prepolymer, the first polyether polyol, and the first filler can be weighed according to the formula, and then put into a planetary stirred tank. The stirring speed is 50 r / min to 400 r / min, the temperature is raised to 100℃ to 130℃, and the water content is reduced to below 500 ppm under vacuum for 1 h to 4 h. The temperature is then lowered to below 60℃, and a UV-resistant additive is added. Optionally, the first coupling agent is also added. The stirring speed is 50 r / min to 400 r / min, and the stirring is carried out under vacuum for 30 min to 90 min. The mixture is then sealed and packaged under nitrogen protection to obtain component A, which has a viscous appearance and uniform texture.

[0056] In some embodiments, the preparation of component B in step S3 specifically includes: placing the second filler in a high-speed planetary dispersion mixer, heating it to 80°C~100°C, dehydrating it under vacuum for 2h~4h until the water content of the second filler drops below 1000ppm, cooling the second filler to room temperature, adding the second isocyanate and the second additive, and mixing them uniformly under vacuum until the viscosity is (5×10⁻⁶). 4 )mPa s~(8×10 4 )mPa s, to obtain component B.

[0057] Preferably, the vacuum level in step S3 is 0.09 MPa or higher.

[0058] Preferably, the stirring rate for uniform mixing in step S3 is 50 r / min to 400 r / min.

[0059] As a non-limiting example of preparing component B, carbon black can be weighed according to the specified ratio and added to a planetary dispersion stirred tank. The temperature is raised to 80℃-100℃, and dehydrated under vacuum for 2-4 hours. The planetary dispersion stirred tank temperature is then lowered to room temperature, and the second isocyanate, second coupling agent, and catalyst are added. The mixture is stirred under vacuum at a speed of 50-400 rpm for 30-120 minutes until homogeneous, until the viscosity reaches (5×10⁻⁶). 4 )mPa s~(8×10 4 )mPa The components are sealed and packaged under nitrogen protection to obtain component B.

[0060] This invention provides an application of the above-mentioned high UV-resistant two-component polyurethane sealant in insulated glass.

[0061] The present invention will be further described below with reference to the embodiments.

[0062] It should be noted that the following are specific embodiments, which describe the content disclosed in this application in more detail. These embodiments are merely illustrative, as various modifications and variations within the scope of the disclosure of this application will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on weight, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.

[0063] The raw materials used in the following examples are from the following sources: All isocyanates, including toluene diisocyanate (TDI-80), diphenylmethane diisocyanate (MDI-50, MDI-100), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), and hexamethylene diisocyanate trimer (HDI trimer), were purchased from Wanhua Chemical Group Co., Ltd.

[0064] The manufacturer of polypropylene glycol is Shandong Lanxing Dongda. The grades are: 200 (PPG-200), 400 (PPG-400), 600 (PPG-600), 1000 (PPG-1000), 1500 (PPG-1500), and 2000 (PPG-2000).

[0065] The manufacturer of polyethylene oxide glycol is Shandong Taiyu Chemical Co., Ltd., with a molecular weight of 200 and a grade of PEG-200; a molecular weight of 400 and a grade of PEG-400; and a molecular weight of 600 and a grade of PEG-600.

[0066] The polycarbonate glycol is manufactured by Asahi Kasei Chemicals Co., Ltd. of Japan, with a molecular weight of 1000 and a grade of T5651; and a molecular weight of 2000 and a grade of T5652.

[0067] The manufacturer of polypropylene triol is Shandong Lanxing Dongda. The molecular weight is 300, and the brand name is MN-300; the molecular weight is 400, and the brand name is MN-400; the molecular weight is 500, and the brand name is MN-500; the molecular weight is 700, and the brand name is MN-700; the molecular weight is 1000, and the brand name is MN-1000.

[0068] The titanium dioxide manufacturer is CITIC Titanium Industry, grade CR-501; the nano zinc oxide manufacturer is Shaanxi Zhongke Nano, grade GG-01; the nano calcium carbonate manufacturer is Guangxi Huana New Material Technology Co., Ltd., grade CCS-23; the heavy calcium carbonate manufacturer is Jiangxi Guangyuan Chemical Co., Ltd., grade HX-1250; and the talc manufacturer is Haiyan Stone Powder Factory, grade HY-9246.

[0069] The UV absorbers are manufactured by Beijing Tiangang (brand names: UV-234, UV-326, UV-328, UV-329, UV-531, UV-630), Wuhan Shuer Biotechnology (brand names: UV-1577, UV-1644), and Jiangsu Yushida (brand name: UV-1988).

[0070] The hindered amine light stabilizers are manufactured by BASF (brand names Tinuvin 770 and Tinuvin 292) and Clariant (brand name Hostavin N30P).

[0071] The carbon black manufacturer is Cabot, and the grades are N220, N330, and N550.

[0072] KH-560, KH-550, and KH-792 in the first coupling agent were all purchased from Jiangxi Chenguang New Materials Co., Ltd.; A-1170 was purchased from Momentive Advanced Materials (China) Co., Ltd.

[0073] The second coupling agent, KH-560, is manufactured by Jiangxi Chenguang New Materials Co., Ltd.; A-LINK35 and A-LINK25 are manufactured by Momentive Advanced Materials (China) Co., Ltd.

[0074] The organometallic catalysts, including dibutyltin dilaurate, stannous octate, lead isooctanoate, zinc bismuth composite catalyst, bismuth isooctanoate, and zinc neodecanoate, were all purchased from Xindian Chemical.

[0075] All other raw materials not specifically mentioned are ordinary commercially available products.

[0076] Example 1 S1: Preparation of prepolymer: Weigh 20g of polypropylene glycol with a molecular weight of 200, 60g of polypropylene glycol with a molecular weight of 400, and 715g of polycarbonate glycol with a molecular weight of 2000, and put them into a reaction vessel. The reaction vessel is heated to 100℃ at a speed of 400r / min and dehydrated for 2h under a vacuum of 0.09MPa or higher until the water content drops below 100ppm. The temperature is then lowered to 50℃, and the reaction vessel is heated to 300r / min. 5g of dibutyltin dilaurate is added and mixed for 5min. Then 200g of TDI-80 is added dropwise over 30min. The reaction vessel is then heated to 80℃ at a speed of 300r / min under nitrogen protection for 4h to obtain the prepolymer. The prepolymer is then sealed and stored for later use. S2: Preparation of Component A: Weigh 400g of the prepared prepolymer, 100g of polypropylene triol with a molecular weight of 300, and 450g of titanium dioxide, and put them into a planetary mixer. The mixer is heated to 130℃ at a speed of 50r / min and vacuumed for 2 hours until the water content drops below 500ppm. The mixture is then cooled to below 60℃, and 10g each of UV-234, UV-531, Tinuvin292, and KH550 are added. The mixture is stirred for 30 minutes at a speed of 400r / min and a vacuum degree of 0.09MPa or higher. The mixture is then sealed and packaged under nitrogen protection to obtain Component A, which has a viscous appearance and uniform texture. S3: Preparation of Component B: Weigh 50g of carbon black N220 and add it to a planetary dispersion stirred tank. Heat to 100℃ and dehydrate for 2 hours under a vacuum of 0.09MPa or higher. Cool the planetary dispersion stirred tank to room temperature, add 945g of MDI-50, 10g of KH-560, and 5g of stannous octoate. Stir at 400r / min under a vacuum of 0.09MPa or higher for 30 minutes until homogeneous and the viscosity is 8×10⁻⁶.4 mPa s, sealed and packaged under nitrogen protection, to obtain component B; S4: Preparation of sealant: Mix the prepared components A and B at a mass ratio of 16:1 until homogeneous, and cure at room temperature to obtain the high UV resistance two-component polyurethane sealant of Example 1.

[0077] Example 2 S1: Preparation of prepolymer: Weigh 150g of polypropylene glycol with a molecular weight of 2000 and 747g of polycarbonate glycol with a molecular weight of 2000, and put them into a reaction vessel. The reaction vessel is heated to 120℃ at a speed of 50r / min and dehydrated for 0.5h under a vacuum of 0.09MPa or higher until the water content is reduced to below 100ppm. The temperature is then lowered to 60℃, and the reaction vessel is heated to 400r / min. 3g of zinc-bismuth composite catalyst is added and mixed for 10min. Then 100g of MDI-50 is added dropwise over 60min. The reaction vessel is then heated to 70℃ at a speed of 500r / min under nitrogen protection for 2h to obtain the prepolymer. The prepolymer is then sealed and stored for later use. S2: Preparation of Component A: Weigh 600g of the prepared prepolymer, 50g of polypropylene triol with a molecular weight of 1000, 149g of titanium dioxide, and 200g of nano zinc oxide, and put them into a planetary mixer. The mixer is heated to 100℃ at a speed of 400r / min and vacuumed for 4h to remove water until the water content is reduced to below 500ppm. The mixture is then cooled to below 60℃, and 1g of UV-1988 is added. The mixture is stirred for 60min at a speed of 50r / min and a vacuum degree of above 0.09MPa. The mixture is then sealed and packaged under nitrogen protection to obtain Component A, which has a viscous appearance and uniform texture. S3: Preparation of Component B: Weigh 10g of carbon black N330 and add it to a planetary dispersion stirred tank. Heat to 80℃ and dehydrate for 4 hours under a vacuum of 0.09MPa or higher. Cool the planetary dispersion stirred tank to room temperature, add 500g of MDI-100, 385g of HDI trimer, 100g of A-LINK35, and 5g of zinc neodecanoate. Stir at 100r / min under a vacuum of 0.09MPa or higher for 60 minutes until the mixture is homogeneous and the viscosity is 5×10⁻⁶. 4 mPa s, sealed and packaged under nitrogen protection, yields component B; S4: Preparation of sealant: Mix the prepared components A and B at a mass ratio of 8:1 until uniform, and cure at room temperature to obtain the high UV resistance two-component polyurethane sealant of Example 2.

[0078] Example 3 S1: Preparation of prepolymer: Weigh 130g of polypropylene glycol with a molecular weight of 1500, 19g of polyethylene glycol with a molecular weight of 200, and 650g of polycarbonate glycol with a molecular weight of 1000, and put them into a reaction vessel. The reaction vessel is heated to 105℃ at a speed of 100r / min and dehydrated for 1.5h under a vacuum of 0.09MPa or higher until the water content drops below 100ppm. The temperature is then lowered to 55℃, and 1g of stannous octoate is added at a speed of 50r / min and mixed for 7min. Then, 200g of MDI-100 is added dropwise over 40min. The reaction vessel is then reacted at 75℃ for 2.5h at a speed of 400r / min under nitrogen protection to obtain the prepolymer, which is then sealed and stored for later use. S2: Preparation of Component A: Weigh 410g of the prepared prepolymer, 60g of polypropylene triol with a molecular weight of 400, 100g of nano zinc oxide, and 400g of heavy calcium carbonate, and put them into a planetary stirring vessel. The stirring speed is 300r / min, the temperature is raised to 130℃, and the vessel is dehydrated under vacuum for 1h until the water content is reduced to below 500ppm. The temperature is then lowered to below 60℃, and 5g of UV-326, 5g of UV-1644, 10g of Tinuvin 770, and 10g of KH-560 are added. The mixture is stirred for 90min at a speed of 100r / min and a vacuum degree of above 0.09MPa. The mixture is then sealed and packaged under nitrogen protection to obtain Component A, which has a viscous appearance and uniform texture. S3: Preparation of Component B: Weigh 39g of carbon black N550 and add it to a planetary dispersion stirred tank. Heat to 85℃ and dehydrate for 3.5h under a vacuum of 0.09MPa or higher. Cool the planetary dispersion stirred tank to room temperature, add 600g of IPDI, 350g of HDI trimer, 1g of dibutyltin dilaurate, and 10g of A-LINK25. Stir for 120min at a speed of 50r / min and a vacuum of 0.09MPa or higher until the viscosity is 7×10⁻⁶. 4 mPa s, sealed and packaged under nitrogen protection, yields component B; S4: Preparation of sealant: Mix the prepared components A and B at a mass ratio of 12:1 until uniform, and cure at room temperature to obtain the high UV resistance two-component polyurethane sealant of Example 3.

[0079] Example 4 S1: Preparation of prepolymer: Weigh 100g of polypropylene glycol with a molecular weight of 1000 and 750g of polycarbonate glycol with a molecular weight of 1000, and put them into a reaction vessel. The reaction vessel is heated to 115℃ at a speed of 200r / min and dehydrated for 1h under a vacuum of 0.09MPa or higher until the water content drops below 100ppm. The temperature is then lowered to 57℃, and 3g of zinc neodecanoate is added at a speed of 150r / min and mixed for 6min. Then, 70g of TDI-80 and 77g of IPDI are added dropwise over 55min. The reaction vessel is then reacted at 73℃ for 2.5h under nitrogen protection at a speed of 350r / min to obtain the prepolymer, which is then sealed and stored for later use. S2: Preparation of Component A: Weigh 590g of the prepared prepolymer, 80g of polypropylene triol with a molecular weight of 500, 200g of titanium dioxide, and 100g of talc powder, and put them into a planetary mixer. The mixer is heated to 125℃ at a speed of 200r / min and dehydrated under vacuum for 3h until the water content drops below 500ppm. The mixture is then cooled to below 60℃, and 10g of UV-328, 5g of UV-630, and 15g of KH-792 are added. The mixture is stirred for 50min at a speed of 350r / min and a vacuum degree above 0.09MPa. The mixture is then sealed and packaged under nitrogen protection to obtain Component A, which has a viscous appearance and uniform texture. S3: Preparation of Component B: Weigh 30g of carbon black N550 and add it to a planetary dispersion stirred tank. Heat to 95℃ and dehydrate for 2.5h under a vacuum of 0.09MPa or higher. Cool the planetary dispersion stirred tank to room temperature, add 918g of HDI trimer, 20g of A-LINK25, 30g of A-LINK35, and 2g of zinc-bismuth composite catalyst. Stir at 300r / min under a vacuum of 0.09MPa or higher for 70min until homogeneous and the viscosity is 6×10⁻⁶. 4 mPa s, sealed and packaged under nitrogen protection, yields component B; S4: Preparation of sealant: Mix the prepared components A and B at a mass ratio of 15:1 until uniform, and cure at room temperature to obtain the high UV resistance two-component polyurethane sealant of Example 4.

[0080] Example 5 S1: Preparation of prepolymer: Weigh 116g of polypropylene glycol with a molecular weight of 600 and 700g of polycarbonate glycol with a molecular weight of 2000, and put them into a reaction vessel. The reaction vessel is heated to 110℃ at a speed of 200r / min and dehydrated for 2h under a vacuum of 0.09MPa or higher until the water content drops below 100ppm. The temperature is then lowered to 52℃, and 4g of lead isooctanoate is added at a speed of 250r / min and mixed for 8min. Then, 180g of IPDI is added dropwise over 40min. The reaction vessel is then reacted at 73℃ for 2.6h under nitrogen protection at a speed of 420r / min to obtain the prepolymer, which is then sealed and stored for later use. S2: Preparation of Component A: Weigh 410g of the prepared prepolymer, 60g of polypropylene triol with a molecular weight of 700, and 500g of titanium dioxide into a planetary mixer. Stir at 100r / min, heat to 125℃, and dehydrate under vacuum for 3.5h until the water content drops below 500ppm. Cool down to below 60℃, add 20g of UV-329 and 10g of KH560, stir at 300r / min and a vacuum of above 0.09MPa for 60min, and seal and package under nitrogen protection to obtain Component A, which has a viscous appearance and uniform texture. S3: Preparation of Component B: Weigh 46g of carbon black N220 and add it to a planetary dispersion stirred tank. Heat to 85℃ and dehydrate for 2.5h under a vacuum of 0.09MPa or higher. Cool the planetary dispersion stirred tank to room temperature, add 600g of MDI-50, 250g of HDI trimer, 60g of KH-560, 40g of A-LINK25, and 4g of lead isooctanoate. Stir for 100min at a speed of 200r / min and a vacuum of 0.09MPa or higher until the viscosity is 7.5×10⁻⁶. 4 mPa s, sealed and packaged under nitrogen protection, yields component B; S4: Preparation of sealant: Mix the prepared components A and B at a mass ratio of 10:1 until uniform, and cure at room temperature to obtain the high UV resistance two-component polyurethane sealant of Example 5.

[0081] Example 6 S1: Preparation of prepolymer: Weigh 60g of polypropylene glycol with a molecular weight of 400, 80g of polyethylene glycol with a molecular weight of 600, and 720g of polycarbonate glycol with a molecular weight of 1000, and put them into a reaction vessel. The reaction vessel is heated to 118℃ at a speed of 200r / min and dehydrated for 1.8h under a vacuum of 0.09MPa or higher until the water content is reduced to below 100ppm. The temperature is then lowered to 60℃, and the reaction vessel is heated to 80r / min. 2g of bismuth isooctanoate is added and mixed for 10min. Then 138g of HDI is added dropwise over 45min. The reaction vessel is then heated to 79℃ at a speed of 320r / min under nitrogen protection for 4h to obtain the prepolymer, which is then sealed and stored for later use. S2: Preparation of Component A: Weigh 530g of the prepared prepolymer, 90g of polypropylene triol with a molecular weight of 500, 200g of nano zinc oxide, and 150g of nano calcium carbonate, and put them into a planetary mixer. The mixer is heated to 130℃ at a speed of 300r / min and dehydrated under vacuum for 1.5h until the water content drops below 500ppm. The mixture is then cooled to below 60℃, and 10g of UV-1577, 5g of Hostavin N30P, and 15g of A-1170 are added. The mixture is stirred for 90min at a speed of 200r / min and a vacuum degree of 0.09MPa or higher. The mixture is then sealed and packaged under nitrogen protection to obtain Component A, which has a viscous appearance and uniform texture. S3: Preparation of Component B: Weigh 20g of carbon black N330 and add it to a planetary dispersion stirred tank. Heat to 82℃ and dehydrate for 4 hours under a vacuum of 0.09MPa or higher. Cool the planetary dispersion stirred tank to room temperature, add 900g of MDI-100, 40g of KH-560, 37g of A-LINK35, and 3g of bismuth isooctanoate. Stir for 120 minutes at a speed of 60r / min and a vacuum of 0.09MPa or higher until the mixture is homogeneous and the viscosity is 5.8×10⁻⁶. 4 mPa s, sealed and packaged under nitrogen protection, yields component B; S4: Preparation of sealant: Mix the prepared components A and B at a mass ratio of 13:1 until uniform, and cure at room temperature to obtain the high UV resistance two-component polyurethane sealant of Example 6.

[0082] Comparative Example 1 The preparation method of Comparative Example 1 is similar to that of Example 2, except that: component A does not contain polyoxypropylene triol and component B does not contain HDI trimer.

[0083] Comparative Example 2 The preparation method of Comparative Example 2 is similar to that of Example 3, except that component A does not contain nano zinc oxide, UV-326, UV-1644 and Tinuvin 770.

[0084] The two-component polyurethane sealants prepared in Examples 1-6 and Comparative Examples 1-2 were subjected to relevant performance tests, and the test results are shown in Table 1 below. All performance tests were conducted in accordance with the test standards in GB / T 29755-2013.

[0085] Table 1

[0086] As shown in Table 1 above, the performance of the high UV-resistant two-component polyurethane sealant prepared in this application meets and exceeds all the requirements of GB / T 29755-2013 standard. Under standard test conditions, this sealant exhibits high tensile bond strength, good elasticity, and no bond failure. In the examples using UV-resistant fillers and UV-resistant additives, after water UV treatment, the tensile bond strength decreased by 3%~15%, while the elongation at maximum tensile bond strength increased by 40%~70%, with no bond failure. After hot air aging, the tensile bond strength increased slightly, while the elongation at maximum tensile bond strength decreased slightly, with no bond failure.

[0087] The water vapor transmission rate of this sealant is 1.5 g / (m²). 2 ·d)~3 g / (m 2 ·d).

[0088] Comparative Example 1, which did not contain polyoxypropylene triol and HDI trimer, failed to meet the tensile bond strength requirements of GB / T29755-2013 standard because it lacked a cross-linked structure, resulting in significant performance variations. In contrast, Comparative Example 2 showed a 63.5% decrease in tensile bond strength and a 3.3-fold increase in water vapor transmission rate, indicating a decline in sealant performance.

[0089] Comparative Example 2, which did not contain nano zinc oxide, UV-326, UV-1644, and Tinuvin 770, still fully met the requirements of GB / T 29755-2013 standard. This is because it did not contain UV-resistant fillers and additives, resulting in significant changes in UV resistance: the tensile bond strength decreased by 22% after water-UV treatment, compared to only 3.6% in Example 3, and the water vapor transmission rate increased by 1.24 times, indicating a decrease in sealant performance.

[0090] The high UV-resistant two-component polyurethane sealant provided in this application utilizes a self-synthesized hydroxyl-terminated prepolymer, which is then mixed with polypropylene triol and reacted with the corresponding isocyanate component. By adjusting the molecular weight and crosslinking density of the final reaction product, the interfacial adhesion between the sealant and glass is first achieved to be greater than the sealant's cohesive force. Furthermore, by using UV-resistant fillers (forming a physical barrier through reflection and scattering of UV light) and UV-resistant additives (UV absorbers efficiently absorb UV light and convert high energy into harmless heat energy through intramolecular hydrogen bond tautomerism; hindered amine light stabilizers scavenge free radicals and do not absorb UV light), UV irradiation can effectively prevent damage to the material's molecular structure, maintaining its original tensile strength, elasticity, adhesion, and sealing properties, ensuring the sealant's safety and reliability, and extending its service life.

[0091] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0092] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A high UV-resistant two-component polyurethane sealant, comprising component A and component B, characterized in that: By weight percentage, component A comprises 40% to 60% prepolymer, 5% to 10% first polyether polyol, 30% to 50% first filler, and 0.1% to 5% first additive; The prepolymer comprises, by weight percentage, 10% to 20% of a first isocyanate, 8% to 15% of a second polyether polyol, 65% to 75% of a polyester polyol, and 0.1% to 0.5% of a first catalyst; The first filler comprises UV-resistant filler accounting for 10% to 50% of the mass of component A; The first auxiliary agent includes a UV-resistant auxiliary agent comprising 0.1% to 3% of the mass of component A; By weight percentage, component B comprises 85% to 95% of a second isocyanate, 1% to 5% of a second filler, and 1.1% to 10.5% of a second auxiliary agent; The mass ratio of component A to component B is (8~16):1; The UV-resistant filler includes titanium dioxide and / or nano zinc oxide; The UV-resistant additives include UV absorbers and / or hindered amine light stabilizers; The first polyether polyol in component A includes polyoxypropylene triol, wherein the molecular weight of the polyoxypropylene triol is one or more of 300, 400, 500, 700 and 1000; The first isocyanate in the prepolymer includes one or more of toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate; The second polyether polyol in the prepolymer includes polypropylene glycol and / or polyethylene glycol, wherein the polypropylene glycol has a molecular weight of one or more of 200, 400, 600, 1000, 1500 and 2000; and the polyethylene glycol has a molecular weight of one or more of 200, 400 and 600. The polyester polyol in the prepolymer includes polycarbonate diol, the polycarbonate diol having a molecular weight of 1000 and / or 2000. The second isocyanate in component B includes one or more of diphenylmethane diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate trimer.

2. The high UV-resistant two-component polyurethane sealant as described in claim 1, characterized in that: The ultraviolet absorber is selected from one or more of benzotriazoles, triazines, benzophenones, and benzylmalonates.

3. A high UV-resistant two-component polyurethane sealant as described in claim 1 or 2, characterized in that: The high UV-resistant two-component polyurethane sealant meets at least one of the following conditions: 1) The first filler in component A further includes one or more of nano-calcium carbonate, heavy calcium carbonate, and talc; 2) The first adjuvant in component A further includes a first coupling agent at a mass of 0% to 2% of component A; 3) The first catalyst in the prepolymer includes an organometallic catalyst; 4) The second filler in component B includes carbon black; 5) The second auxiliary agent in component B includes a second coupling agent comprising 1% to 10% of the mass of component B and a second catalyst comprising 0.1% to 0.5% of the mass of component B, wherein the second catalyst comprises an organometallic catalyst.

4. The high UV resistance two-component polyurethane sealant as described in claim 3, characterized in that: The high UV-resistant two-component polyurethane sealant meets at least one of the following conditions: 1) The organometallic catalyst includes one or more of dibutyltin dilaurate, stannous octanoate, lead isooctanoate, zinc bismuth composite catalyst, bismuth isooctanoate, and zinc neodecanoate; 2) The first coupling agent in component A includes one or more of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-aminopropyltriethoxysilane, bis-(γ-trimethoxysilylpropyl)amine and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane; 3) The second coupling agent in component B includes one or more of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 3-isocyanate-propyltrimethoxysilane and 3-isocyanate-propyltriethoxysilane.

5. A method for preparing a high UV-resistant two-component polyurethane sealant, characterized in that, The preparation method is used to prepare a high UV-resistant two-component polyurethane sealant as described in any one of claims 1 to 4, and the preparation method includes the following steps: S1: Preparation of the prepolymer: The first isocyanate is reacted with the second polyether polyol and the polyester polyol to obtain the prepolymer; S2: Preparation of component A: The prepolymer, the first polyether polyol, the first filler and the first auxiliary agent are mixed and then subjected to heat treatment and dehydration treatment to obtain component A; S3: Preparation of component B: After dehydrating the second filler, the second isocyanate and the second auxiliary agent are added and mixed evenly to obtain component B; S4: Preparation of sealant: Mix component A and component B at a mass ratio of (8~16):1 and then cure to obtain the high UV resistant two-component polyurethane sealant.

6. The method for preparing a high UV-resistant two-component polyurethane sealant as described in claim 5, characterized in that: The preparation method satisfies at least one of the following conditions: 1) The preparation of the prepolymer in step S1 specifically includes: mixing the second polyether polyol and the polyester polyol and heating to 100℃~120℃, dehydrating under vacuum for 0.5h~2h, cooling down and adding the second catalyst, adding the first isocyanate and stirring to react, thereby obtaining the prepolymer; 2) The preparation of component A in step S2 specifically includes: mixing the prepolymer, the first polyether polyol and the first filler and heating to 100℃~130℃, dehydrating under vacuum for 1h~4h until the water content drops below 500ppm to obtain a premix; cooling the premix to below 60℃, adding the first auxiliary agent, and mixing and stirring evenly under vacuum to obtain component A; 3) The preparation of component B in step S3 specifically includes: placing the second filler in a high-speed planetary dispersion mixer, heating it to 80℃~100℃, dehydrating it under vacuum for 2h~4h until the water content of the second filler drops below 1000ppm, cooling the second filler to room temperature, adding the second isocyanate and the second additive, and mixing them evenly under vacuum until the viscosity is (5×10⁻⁶). 4 )mPa s~(8×10 4 )mPa s, to obtain component B.

7. The method for preparing a high UV-resistant two-component polyurethane sealant as described in claim 6, characterized in that: The preparation method satisfies at least one of the following conditions: 1) The temperature at which the second catalyst is added in step S1 is 50℃~60℃; 2) The first isocyanate is added in step S1 by dripping, and the dripping time is 30 min to 60 min; 3) In step S1, the reaction temperature for adding the first isocyanate is 70℃~80℃, the reaction time is 2h~4h, and the reaction atmosphere is nitrogen atmosphere. 4) The stirring rate for adding the first isocyanate in step S1 is 300 r / min to 500 r / min; 5) The vacuum level described in step S2 is above 0.09 MPa; 6) The mixing speed in step S2 is 50 r / min to 400 r / min; 7) The vacuum level of the vacuum conditions described in step S3 is above 0.09 MPa; 8) The stirring speed for uniform mixing in step S3 is 50 r / min to 400 r / min.

8. The application of a high UV-resistant two-component polyurethane sealant as described in any one of claims 1 to 4 in insulated glass.

Citation Information

Patent Citations

  • Single-component silicane-modified polyurethane sealant and preparation method thereof

    CN103146336A

  • Two-component polyurethane sealant for insulating glass and preparation method thereof

    CN108795363A